The formula for the nth term of an arithmetic sequence can be found using the formula a Subscript n Baseline = a Subscript 1 Baseline + (n minus 1) d. Which of the following is equivalent to this equation? n = a Subscript n Baseline + a Subscript 1 n = StartFraction a Subscript n Baseline + a Subscript 1 Baseline minus 3 Over d EndFraction n = a Subscript n Baseline minus a Subscript 1 n = a Subscript n Baseline minus a Subscript 1 Baseline + d Over d EndFraction

Respuesta :

Answer:

  n = [StartFraction] a Subscript n Baseline minus a Subscript 1 Baseline + d Over d EndFraction

Step-by-step explanation:

I personally find it easier to read using math symbols. Punctuation would help, too, to separate answer choices.

  [tex]a_n=a_1+(n-1)d\\\\a_n-a_1=nd-d \qquad\text{subtract $a_1$}\\\\a_n-a_1+d=nd \qquad\text{add $d$}\\\\n=\dfrac{a_n-a_1+d}{d} \qquad\text{divide by the coefficient of n}[/tex]

This seems to match the last answer selection.

Answer:

D) n=an-a1+d/d

Step-by-step explanation: